Sorption Potential of Litchi chinensis for Aqueous Metanil Yellow Solution - Adnan, Ahmad; Shahid, Samina; A. Qureshi, Fahim; Ahmad, Iftikhar; Faiza Shamsheer, Hafiza; Rehman, Shafiq-ur (Asian Journal of Chemistry, 2011)
Litchi chinensis stem bark was used as biosorbent for the removal of metanil yellow from aqueous solution. Biosorbent was washed with 80 % methanol and hot tap water respectively and then activated by boiling with 6 N HCl. After activation biomass was washed several times with distilled water and dried at 80 ºC over night. Different parameters such as initial pH, dye concentration, sorbent dosage, ion strength, particle size and time period were studied. pH 2 was found optimum for this study. Metanil yellow were removed 97.6 % at pH 2.0. Langmuir model was applied on the isothermal data for biosorption. FTIR spectra showed that amino group adsorbed the dye thorough the electrostatic attraction between the positive charge of dye and negative charge of biosorbent.